ANALISIS SISTEM TANGGAP DARURAT KEBAKARAN DI AREA PRODUKSI INDUSTRI KIMIA PT. X TAHUN 2015 - Ifan Zanuar Ashary; Bina Kurniawan; Baju Widjasena (Jurnal Kesehatan Masyarakat (Undip), 2017)
In indonesia, some of the accident there has been caused by dangerous chemicals, for example because of methane gas explosion in west sumatra, rubber and forth in a factory fire. Industry especially those who manage the level of harmful substances having a high fire risk. Causing industrial fire in a very large losses related to asset value because of high , the process of production and employment opportunities. PT . X is one of a company that has the potential dangers of fire and blasting great considering the materials used are among other combustible material ethanol, benzene, acetate of manganese, spiritus and so forth. The purpose of this research is analyzing emergency response system of fire in the area of the production of the chemical industry PT. X 2015. The research is descriptive qualitative research by in-depth interviews and observations. The subject of this research is 3 main informants and 2 informants triangulation.The research results show that in the implementation of the emergency response systems fire, PT. X have had emergency response organization which is made up of all the employees who has a duty and the functions of each that have received training every year that is held by the company and has also have a procedure emergency response according to the writer. director general of the ppk no .84/ 2012. Protection system active consist of apar , a fire hydrant and a yard that are already in accordance with criteria NFPA 10 and NFPA 14, also equipped with alarm tocsin. PT. X has also provided evacuation routes and scene of the evacuation. In this case the researchers suggest that exercise program continue and done a simulation unexpected preparedness in order to assess personnel and assess the achievement of emergency response systems fire.